Building digital civility of Indonesian net citizens from a digital citizenship perspective - Makassar, Najla; Habibah, Siti Maizul (C-DISC, 2024)
The Digital Civility Index (DCI) survey, conducted by Microsoft in 2020, was based on the findings of its annual Civility, Safety and Interactions Online study. The objective of the DCI survey, or Digital Civility Index, is to ascertain and enhance the digital civility of internet users globally with regard to their online communication. The results of the survey revealed that Indonesian netizens exhibited the lowest level of digital civility among their Southeast Asian counterparts. The objective of this article is to provide an understanding of the digital civility of netizens in their online interactions, with a view to facilitating constructive interactions based on a digital citizenship perspective. This article was prepared using the bibliography method. The results of the study demonstrate that the digital civility of Indonesian netizens is deficient due to their limited capacity to interact online, which renders them susceptible to the propagation of misinformation. Proficient netizens must possess the capacity to navigate novel challenges by upholding human rights, embracing cultural differences, and demonstrating the requisite digital intelligence competencies, namely information literacy, media and digital empathy.